Can maternal hormones play a significant role in delivery mode?. (3rd October 2022) - Pappa, Christina; Gkrozou, Fani; Dimitriou, Evangelos; Tsonis, Orestis; Kitsouli, Aikaterini; Varvarousis, Dimitrios; Xydis, Vasileios; Paschopoulos, Minas; Kitsoulis, Panagiotis
Abstract: The aim of this study was primarily to evaluate the levels of progesterone, oestradiol and relaxin during different delivery modes and secondarily to assess specific traits and changes in maternal pelvic dimensions during pregnancy and childbirth, in correlation with foetal size and maternal hormonal profile. Nulliparous women ( n  = 448) were evaluated at three different stages, during first trimester, at the time of admission for childbirth and finally just before childbirth. Each examination included clinical internal pelvimetry, blood sample collection for defining the hormones levels in peripheral maternal circulation and ultrasonographic measurements of specific variables of the pubic symphysis and the foetus. We included 304 nulliparous women divided in three groups. According to our results, there was statistically significant difference at the mean progesterone, oestradiol and relaxin range during different modes of childbirth ( p -value < .01). We also found significant correlation between the newborn's weight and the changes in pubic symphysis dimensions. However, no significant association was noted between maternal hormones studied and the changes in pelvic dimensions. IMPACT STATEMENT: What is already known on this subject? Mode of childbirth can be affected by various aspects, like maternal pelvic anatomy, foetal size and hormonal status at the time of labour. Hormonal fluctuations along with mechanical forces caused by the foetus are believed to lead to morphological alterations to promote natural vaginal childbirth. What do the results of this study add? Our results clearly showed that successful vaginal delivery is characterised by the prevalence of a hyperoestrogenic environment with higher values of intrapartum oestradiol range and significant increase in maternal serum relaxin levels. We also proved that progesterone levels do not decrease during vaginal childbirth, and we concluded that foetal size seems to be the most crucial factor causing alterations in maternal pelvis during parturition. What are the implications of these findings for clinical practice and further research? Our findings could form part of a set of key factors included in future algorithms or computerised biomechanical models for predicting potential childbirth mode. Larger multicenter studies should confirm our results and evaluate their clinical significance in the decision making to ensure safe childbirth and optimal maternal and perinatal outcomes.